The Effect of Moderate Heat on Rat Pituitary ACTH Cells: Histomorphometric, Immunofluorescent and Hormonal Study - Popovska-Perčinić, Florina; Jarić, Ivana; Pendovski, Lazo; Nataša, Ristić; Trifunović, Svetlana; Milošević, Verica; Ajdžanović, Vladimir (Walter de Gruyter GmbH, 2017)
AbstractIn areas with moderate continental climate, increased average ambient temperature during the summer represents a stressogenic factor that affects the hypothalamo-pituitaryadrenocortical axis in mammals. Therefore, we wanted to examine the effects of 4 days of constant exposure to moderately elevated ambient temperature (35 ± 1oC) on the histomorphometric and immunofl uorescent characteristics, as well as on the hormonal secretion of pituitary corticotropes (ACTH) cells in adult male rats. In comparison with the controls kept at 20 ± 2oC, a signifi cant increase (p<0.05) of the absolute and relative pituitary weight (23.1% and 36.1%, respectively) was registered after exposure to heat. The localization, as well as the shape of the ACTH cells in the heat exposed group was not signifi cantly altered, but their immunopositivity was weaker. After 4 days of heat exposure, a weaker signal confi rmed the relative fl uorescence intensity of the ACTH cells (15.3%, p<0.05). In heat exposed rats, an increase of the cellular and nuclear volumes of immunolabelled ACTH cells and decrease of their volume density (6.9%, 14.3% and 20.0%, respectively; p<0.05) was registered. Observed histomorphometric and immunofl uorescent features of the pituitary ACTH cells were in accordance with the increased (p<0.05) value of plasma adrenocorticotropic hormone (ACTH) by 23.7% compared to the control rats. It can be concluded that the 4-day exposure to moderately elevated ambient temperature intensifi es pituitary ACTH secretion in adult male rats.